A new vector draft method for harmonic source detection at point of common coupling - abdullah, abdul rahim; goh, zai peng; Ab Ghani, Sharin; JOPRI, MOHD HATTA (2014)
In modern power networks, the issue of power quality (PQ) is becoming very important because of the increasing of load which sensitive to current disturbances. This is mainly due to the increasing use of non-linear power electronic devices draws nonsinusoidal current and creating a current distortion. As a result there is increasing need for PQ to be monitored to establish the type, sources and locations of PQ disturbances, allowing remedial measures to be taken. Consequently, harmonic is one of the most concerned power quality disturbances. The detection of harmonic source is necessary for power quality strategy development. This paper introduces a new single-point measurement method to estimate the harmonic source by using phase spectrogram (PS) and frequency spectrogram (FS) based on a vector draft method. A measurement at the point of common coupling (PCC) with harmonic distortion is done by simulation via PSCAD. Then PSCAD’s data are analyzed by using spectrogram in MATLAB. To be precise, voltage and current waveforms are normalized with fundamental magnitude respectively. Next, the normalized voltage and current are plotted on the vector draft to estimate the perpendicular point between the vectors. The center point of the normalized voltage is the boundary between downstream and upstream. The harmonic source can be detected base on the perpendicular point’s location that fall on the particular region. The comparison between actual and power direction result have been conducted. Finally, the proposed method is similar with the actual result and more truthful than power direction method.